GEOPOLYMER CONCRETE: IT'S RESPONSE TOWARDS ALKALI SILICA REACTION (ASR) - ABD RAZAK, SITI NOORIZA (2015)
Geopolymer was introduced by Davidovit in 1978 as a binder that produced by polymeric synthesis of the alkali activated material like fly ash or rice husk ash. Although geopolymer possess very good mechanical strength and durability against attacks from acid, chloride, sulphate and fire, but there some issues that remain unknown over time which is alkali silica reaction (ASR). ASR is one of the reactions that could affect the strength and durability of OPC based structure, either made as concrete or mortar. This research aim is to determine the effect ofASR in geopolymer made from fly ash with incorporation of Microwave Incinerated Rice Husk Ash (MIRHA) in the presence of reactive aggregate. Geopolymer specimens were prepared using Class F fly ash with incorporation of Microwave Incinerated Rice Husk Ash (MIRHA) to replace percentage of fly ash content as binder.